CoNiO2/Co4N Heterostructure Nanowires Assisted Polysulfide Reaction Kinetics for Improved Lithium–Sulfur Batteries. Issue 4 (11th December 2021) - Pu, Jun; Gong, Wenbin; Shen, Zhaoxi; Wang, Litong; Yao, Yagang; Hong, Guo
Abstract: The "shuttle effect" of soluble polysulfides and slow reaction kinetics hinder the practical application of Li–S batteries. Transition metal oxides are promising mediators to alleviate these problems, but the poor electrical conductivity limits their further development. Herein, the homogeneous CoNiO2 /Co4 N nanowires have been fabricated and employed as additive of graphene based sulfur cathode. Through optimizing the nitriding degree, the continuous heterostructure interface can be obtained, accompanied by effective adjustment of energy band structure. By combining the strong adsorptive and catalytic properties of CoNiO2 and electrical conductivity of Co4 N, the in situ formed CoNiO2 /Co4 N heterostructure reveals a synergistic enhancement effect. Theoretical calculation and experimental design show that it can not only significantly inhibit "shuttle effect" through chemisorption and catalytic conversion of polysulfides, but also improve the transport rate of ions and electrons. Thus, the graphene composite sulfur cathode supported by these CoNiO2 /Co4 N nanowires exhibits improved sulfur species reaction kinetics. The corresponding cell provides a high rate capacity of 688 mAh g −1 at 4 C with an ultralow decaying rate of ≈0.07% per cycle over 600 cycles. The design of heterostructure nanowires and graphene composite structure provides an advanced strategy for the rapid capture–diffusion–conversion process of polysulfides. Abstract : Uniform CoNiO2 /Co4 N heterostructure nanowires are prepared by a controlled hydrothermal and nitriding process. The in situ heterostructure with the continuous interface combine the strong polysulfide adsorption of CoNiO2 and the high electrical conductivity of Co4 N. It not only effectively alleviates the "shuttle effect", but also greatly improves the reaction dynamics of the battery.